ANALISIS PENGARUH LABEL HALAL, BRAND DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN DI KOTA MEDAN - Ian Alfian; Muslim Marpaung (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2017)
This study aims to determine how influence the direct and indirect variable halal label, brand / brand images and prices on consumer purchasing decisions Muslims in the city of Medan (Study in the subdistrict of Medan Petisah). Methods used quantitative approach using path analysis with multiple linear regression model is supported by test models and statistical test by using SPSS version 17. This research showed that approximately 65.1% variable halal label, brand / brand image and price influence consumer purchase decisions Muslims in the city of Medan (a case study in the district of Medan Petisah), while 34.9% is explained by other factors. Next that approximately 59,7% variable halal label and brand influence prices, while 40,3% is explained by other factors. The results show the significance of the indirect impacts their indirect effect of variable halal label and brand / brand image on purchase decisions through the price significantly.